2016
DOI: 10.1002/jbm.a.35933
|View full text |Cite
|
Sign up to set email alerts
|

Porous 3D implants of degradable poly‐3‐hydroxybutyrate used to enhance regeneration of rat cranial defect

Abstract: The study describes preparation and testing of porous 3D implants of natural degradable polymer of 3-hydroxybutyric acid P(3HB) for regeneration of bone tissue defects. The ability of the P(3HB) implants to favor attachment and facilitate proliferation and directed differentiation of mesenchymal stem cells (MSCs) was studied in the culture of MSCs isolated from bone marrow and adipose tissue. Tissue-engineered hybrid systems (grafts) constructed using P(3HB) and P(3HB) in combination with osteoblasts were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…The ability of porous 3D implants P(3HB) to favor attachment and facilitate proliferation and directed differentiation of mesenchymal stem cells (MSCs) was studied in the culture of MSCs isolated from bone marrow and adipose tissue. And results suggest that P(3HB) has good potential as osteoplastic material for reconstructive osteogenesis [25].…”
Section: Applications As Medical Implant Materialsmentioning
confidence: 93%
“…The ability of porous 3D implants P(3HB) to favor attachment and facilitate proliferation and directed differentiation of mesenchymal stem cells (MSCs) was studied in the culture of MSCs isolated from bone marrow and adipose tissue. And results suggest that P(3HB) has good potential as osteoplastic material for reconstructive osteogenesis [25].…”
Section: Applications As Medical Implant Materialsmentioning
confidence: 93%
“…A thin fibrous capsule (~ 100 μm) is formed during a month and is resorbed once the samples have biodegraded [1922]. Many studies revealed a low lymphocyte count or virtually no lymphocytes (in particular, T lymphocytes) at the PHB insertion site, indicating that the immune reaction to this polymeric biomaterial is either significantly reduced or absent [2326]. It was demonstrated that deeply purified PHB and PHBV also exhibit good hemocompatibility, so they can be used to produce blood-contacting medical devices: patches for the pericardial wall, the pulmonary artery, and the right atrium, as well as biodegradable coronary stents [2530].…”
Section: The Biological Activity Of Polyhydroxyalkanoatesmentioning
confidence: 99%
“…Implantation of the PHB-based porous scaffold leads to vigorous vascularization of the scaffold and emergence of islets of the bone tissue newly formed from the granulation tissue in its pores [23, 24, 31]. Evaluation of the expression levels of various cytokines and other markers of inflammation in the implantation site of medical devices based on PHB (and its copolymer PHBV) revealed reduced expression levels of proinflammatory cytokines (interleukins, tumor necrosis factor, monocyte chemoattractant protein, inducible nitric oxide synthase, and C-reactive protein) compared to those for other materials and increased expression of genes encoding various proteins (type I collagen, caveolin-1, cytokeratin, heparan sulfate proteoglycan, thrombomodulin, and prostacycline), which are markers of regenerative processes taking place in cardiac, vascular, intestinal, neural, and osseous tissues [23, 25, 27, 28, 3235]. However, chronic inflammatory response to the implantation of PHB-based devices (e.g., coronary stent prototypes) was observed in some cases.…”
Section: The Biological Activity Of Polyhydroxyalkanoatesmentioning
confidence: 99%
“…Powerful osteogenic potential of autogenous bone makes this graft be regarded as the "gold standard"; however, this graft has disadvantage in limited quantity and donor morbidity (1). It is, thus, required to find three-dimensional (3D), biodegradable and biocompatible scaffolds mimicking the bone tissue architecture for tissue engineering applications as an alternative (2,3). Although soft scaffolds (e.g., hydrogels or collagen sponge) have been predominantly used in the tissue engineering filed, these are limited by their poor mechanical properties.…”
Section: Abstract Background/aim: As An Alternative Materials To the mentioning
confidence: 99%